2019
DOI: 10.4254/wjh.v11.i1.19
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of primary sclerosing cholangitis in children

Abstract: Primary sclerosing cholangitis (PSC) is a rare disease of stricturing and destruction of the biliary tree with a complex genetic and environmental etiology. Most patients have co-occurring inflammatory bowel disease. Children generally present with uncomplicated disease, but undergo a variable progression to end-stage liver disease. Within ten years of diagnosis, 50% of children will develop clinical complications including 30% requiring liver transplantation. Cholangiocarcinoma is a rare but serious complicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 132 publications
0
32
0
5
Order By: Relevance
“…Our efforts were based on publications in pediatric literature suggesting benefit of vancomycin in sclerosing cholangitis. 16,[33][34][35] In light of these findings, we have modified our counseling in the post-transplant setting regarding the risks of Cryptosporidium in our patients. We recommend abstaining from public water parks and freshwater swimming for the first 12 months after transplant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our efforts were based on publications in pediatric literature suggesting benefit of vancomycin in sclerosing cholangitis. 16,[33][34][35] In light of these findings, we have modified our counseling in the post-transplant setting regarding the risks of Cryptosporidium in our patients. We recommend abstaining from public water parks and freshwater swimming for the first 12 months after transplant.…”
Section: Discussionmentioning
confidence: 99%
“…This was in concert with UDCA (patients 4 and 5) or following an ineffective UDCA course (patient 3). Our efforts were based on publications in pediatric literature suggesting benefit of vancomycin in sclerosing cholangitis 16,33‐35 . Proposed mechanisms of action for vancomycin efficacy include changes to disease‐related enteral microbial populations and direct effects on the immune system—including increased peripheral regulatory T‐cell populations 35 .…”
Section: Discussionmentioning
confidence: 99%
“…PSC may present in an IBD patients even after colectomy. Multiple gallbladder abnormalities in the course of primary sclerosing cholangitis including: dilatation (15%), gallstones (25%), cholecystitis, hydrops, polyps (4-6%), carcinoma (2.5-3.5%) are observed more often in patients [2,8,17,22,29,30].…”
Section: Clinical Picturementioning
confidence: 99%
“…Liver transplantation is a life-saving procedure with generally good outcomes, however, up to 16% of paediatric patients are affected by recurrent primary sclerosing cholangitis (rPSC) after transplantation. The indications for liver transplantation in PSC are similar to other liver diseases and transplanted with a qualifying MELD/PELD score in a patient with cirrhosis [11,29,51].…”
Section: Liver Transplantationmentioning
confidence: 99%
“…Though a rare disease, PSC is the fifth leading indication for liver transplantation (LT) in the United States and a major indication in other countries[ 1 , 3 - 5 ]. Moreover, no medical therapy has been shown to significantly delay PSC progression; indeed, it has been suggested that PSC treatments are one of the greatest unmet needs in hepatology[ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%